2016
DOI: 10.3390/nu8030177
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient Distribution and Dietary Sources in the Spanish Population: Findings from the ANIBES Study

Abstract: Our aim was to analyze dietary macronutrient intake and its main sources according to sex and age. Results were derived from the ANIBES (“Anthropometry, Intake and Energy Balance in Spain”) cross-sectional study using a nationally-representative sample of the Spanish population (9–75 years old). Mean dietary protein intake was 74.5 ± 22.4 g/day, with meat and meat products as the main sources (33.0%). Mean carbohydrate intake was 185.4 ± 60.9 g/day and was higher in children and adolescents; grains (49%), main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
89
6
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(121 citation statements)
references
References 44 publications
24
89
6
2
Order By: Relevance
“…Seasonality in the consumption of beverages is very important, thus, the fieldwork was performed from September to November as a period in which beverage consumption is usually more stable (18). Total energy intake (14) and macronutrients distribution for the other foods groups (19) was already shown in previous publications.…”
Section: Discussionsupporting
confidence: 74%
“…Seasonality in the consumption of beverages is very important, thus, the fieldwork was performed from September to November as a period in which beverage consumption is usually more stable (18). Total energy intake (14) and macronutrients distribution for the other foods groups (19) was already shown in previous publications.…”
Section: Discussionsupporting
confidence: 74%
“…The latest Spanish data on infants and young children are described in the ENALIA, ALSALMA and ANIBES studies. In all cases, the reported protein intake was also higher than the available recommendations [24,52,53].…”
Section: Nutrient Profile and Distributionmentioning
confidence: 68%
“…Similarly, in the ANIBES study, the total fat intake was higher (37.9%) than the EFSA recommendations [53]. Moreover, a systematic review conducted by Wanden-Berghe et al, in 2015 in Spanish population 5 to 81 years old, found that the mean energy contribution from macronutrients was 18% protein, 44% carbohydrates and 38% fat.…”
Section: Nutrient Profile and Distributionmentioning
confidence: 77%
“…The Spanish adult population consumes a mean of 246 ml/day of sugar-sweetened beverages, including soft drinks, fruit juices and fruit drinks. 7 This consumption is higher among adolescents, among whom it rises to 450 ml/day 8 and provides more than 6% of their total caloric intake, 9 thereby contributing to the high prevalence obesity in Spain. 10 In 2016, the Minister of Inland Revenue therefore announced the establishment of a tax on sugar-sweetened beverages in Spain, but the Government withdrew the proposal in the face of pressure from the soft drink industry and sugar beet sector.…”
Section: Introductionmentioning
confidence: 99%